(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This article reports on a Systematic Literature Review with database automated search. The objective is to systematically map the national literature, through stricto sensu postgraduate dissertations and theses, produced in the period from 2006 to 2002 that used the stimulus equivalence model, teaching of conditional relations and emerging performance tests for evaluation and establishment of mathematical repertoires. 20 studies were considered results, identifying emphasis, context, methodology, and most cited results. The results show the disparity in production in the regions where the work is carried out. The studies reflected on early childhood education and elementary school, with contents of fractions, mathematical operations (addition and subtraction), oral counting and numerical and ordinal relations. The procedures used more were Matching-to-Sample - MTS and/or Constructed Response Matching-to-Sample - CRMTS. The state of the art proposes recommendations for future studies, mainly in secondary and higher education.